Seroprevalences and disposals of blood bags in a blood bank in Goiânia-GO (Research, Society and Development, 2021)
The disposal of blood bags, as well as their derivatives, follows the rules of Anvisa, which considers contamination, expiration dates, inadequate collections, among others. In Brazil, the serologic screening of transfusion materials is mandatory, and serology for Chagas, Hepatitis B, Hepatitis C, HIV, HTLV I, HTLV II and Syphilis is investigated in every donor, and if present, they make the candidate unsuitable for donation, either definitely or temporarily. Due to the emergence and re-emergence of such infectious and contagious diseases, it is even more important to assess the prevalence of these diseases in order to avoid further contamination, as well as to enable quantification and provide data for the realization of public health strategies aimed at reducing their emergency, thus reducing these diseases and optimizing the availability and quality of hemotherapeutic products and services, which are necessary for various situations, such as transfusions for patients with hypovolemic shock, sickle cell anemia or deficiencies in clotting factors (among other factors). This study evaluated the prevalence of inability of candidates for blood donation in a blood bank in Goiânia from 2017 to 2019, aiming to analyze the collected data and compare with national epidemiological data.